A Closing Window of Opportunity to Save a Unique Marine Ecosystem - Kleinhaus, Karine; Voolstra, Christian R.; Meibom, Anders; Amitai, Yael; Gildor, Hezi; Fine, Maoz (Frontiers in Marine Science, 2020)
Five years in the making, a massive oil spill of 1 million barrels is imminent in the Red Sea off the coast of Yemen. Emergent action must be taken by the United Nations and its International Maritime Organization (IMO) to remove the oil, despite regional political tensions, as a spill will have disastrous environmental and humanitarian consequences, especially if it occurs during winter. With millions of barrels of oil passing through the Red Sea each day, a regional strategy must be drafted for leak prevention and containment that is specific to the Red Sea’s unique ecosystems, unusual water currents, and political landscape.